Connecting the Dots. Between Ape and Human: An Anthropologist on the Trail of a Hidden Hominoid by Gregory Forth - Meldrum, Jeffrey (Journal of Scientific Exploration, 2023)
Dr. Gregory Forth’s latest publication, Between Ape and Human, is his first monograph directed to a general audience, while maintaining a scholarly approach. It provides a more accessible, welcome and authoritative voice addressing the timely anthropological question, “Are other hominins alive today?” (Forth, 2012). His decades of enthnographic field research are juxtaposed with the discovery of fossil hominins on the eastern Indonesian island of Flores. The discovery of 50,000-year-old skeletal remains of an australopoithecine-like hominin seemed to lend substance to the traditional and contemporary stories of hairy diminutive ape-men that may survive to this day. The announced discovery of Homo floresiensis came on the eve of a department seminar as part of my bid for promotion to full professor. I hastily prepared and added a preamble to my presentation, highlighting the implications of the discovery for the prospects of the persistence of relict hominoids, including the sasquatch, which has been a central element of my research program. Based on feedback following my presentation, the bearing of the unfolding of the discovery of floresiensis for my research, considered questionable by many of my colleagues, was utterly lost on them. Indeed, the discovery of the “Hobbit”, and other indications of additional persistent hominin lineages of an ever-bushier hominin tree, has likewise been seemingly lost on the anthropological community at large, as well. This in spite of isolated comments, such as Nature’s managing editor, Henry Gee’s (2004), “The discovery that Homo floresiensis survived until so very recently, in geological terms, makes it more likely that stories of other mythical, human-like creatures such as yetis are founded on grains of truth…Now, cryptozoology, the study of such fabulous creatures, can come in from the cold.”